Primary Health Care Software-A Computer Based Data Management System - Tuli K; Kapoor S K; Nath L M (Wolters Kluwer Medknow Publications, 1990)
Realising the duplication and time consumption in the usual manual system of data collection necessitated experimentation with computer based management system for primary health care in the primary health centers. The details of the population as available in the existing manual system were used for computerizing the data. Software was designed for data entry and analysis. It was written in Dbase III plus language. It was so designed that a person with no knowledge about computer could use it, A cost analysis was done and the computer system was found more cost effective than the usual manual system.